Against professional advice: treatment attrition among pregnant methamphetamine users - Terplan M; Albrecht JS; Lindsay B (Dove Medical Press, 2011)
Brianna Lindsay1, Jennifer Albrecht1, Mishka Terplan1,21Department of Epidemiology and Public Health, University of Maryland, 2Department of Obstetrics, Gynecology, and Reproductive Science, University of Maryland School of Medicine, Baltimore, MD, USAAbstract: Pregnant methamphetamine users who leave substance use treatment against professional advice may be at risk of poorer health outcomes. To examine the hypothesis that methamphetamine use during pregnancy may be associated with leaving substance use treatment against professional advice, the 2006 Treatment Episode Data Set was analyzed. A logistic regression adjusting for age, race, service setting, prior substance abuse treatment, criminal justice referral, and education was conducted. Inclusion criteria were met by 18,688 pregnant admissions; 26.4% identified methamphetamines as their primary substance of use. Frequency of use was identified as an effect modifier, therefore results were stratified by less than weekly use and weekly or more use. Methamphetamine use was significantly associated with leaving treatment against professional advice regardless of usage level. However, the odds of leaving treatment were greater among women using methamphetamine less than weekly. Further investigation into this association may be warranted due to the complications that may result from methamphetamine use during pregnancy.Keywords: pregnancy, methamphetamines, treatment, attrition